Biodegradation of low density polyethylene by the action of a microbial consortium isolated from a landfill, Lima, Peru - Uribe, Diego (2010)
In this paper, we describe the isolation and biodegradation activity of microorganisms on low density polyethylene. The microorganisms were collected from plastic materials with evidence of deterioration from a landfill. The samples were filtered and selected in a mineral salts medium at pH 5.5 and 7 for bacteria and fungi respectively. Six strains were isolated, identified as Pseudomonas sp. Hyalodendron sp., Penicillium sp. and Rhodotorula sp. Microbial activity was evidenced by changes in the infrared spectrum of polyethylene with respect to the polymer without treatment. Reduction of carbonyl index (83.89% at pH 7 and 4.08% at pH 5.5) and double bonds index (19.77% at pH 7 and 6.47% at pH 5.5) were observed. Finally we determined the percentage of weight lost by the polyethylene subjected to activity of the strains, with a decrease of 5.4% at pH 7 and 4.8% at pH5, 5.